Delineating and characterizing critical habitat for the Eastern Pacific olive ridley turtle (Lepidochelys olivacea): Individual differences in migratory routes present challenges for conservation measures - Figgener, Christine; Bernardo, Joseph; Plotkin, Pamela T. (Frontiers in Ecology and Evolution, 2022)
The effective conservation of highly migratory marine species is only possible if core areas of activity and critical habitat can be identified within the vast and dynamic oceanic environment and later on used to delineate marine protected areas (MPAs). However, gathering population-level data and identifying universal patterns within a species or population can be difficult when only a small sample size exists and individuals are not ecological interchangeably. In addition, the open ocean beyond the Economic Exclusion Zones (EEZ) of a country is considered the high-seas and is not part of any jurisdiction and therefore challenging to govern by laws. Granting protection to species using these waters is sometimes virtually impossible. Another challenge is the dynamic nature of the oceanic environment. MPAs are usually based on spatially explicit and static areas, but migratory routes can shift following available food, currents, and temperatures or else, potentially rendering designated areas useless. The red-listed olive ridley turtle is known for its nomadic migratory and feeding behaviour and a divergent nesting strategy among females. Our study used two approaches to identify critical habitat for the population nesting in Costa Rica and feeding in the Eastern Tropical Pacific. One was based on a static Kernel Density Approach to identify core areas. The other was a habitat preference model that took into account changing environmental variables such as sea surface temperature and chlorophyll-a concentrations. We were able to identify core areas at the population level by pooling two datasets and increasing our sample size. Our habitat preference model showed a high correlation of olive ridley presence with all tested environmental variables, except chlorophyll-a concentration. Our results reveal that olive ridleys use mainly regions that fall within EEZs and, therefore, the jurisdiction of six countries in Central America and provide an essential conservation tool.